2020
DOI: 10.3390/app10238750
|View full text |Cite
|
Sign up to set email alerts
|

Soil Stabilization Using Waste Paper Fly Ash: Precautions for Its Correct Use

Abstract: This paper deals with the valorization of waste paper fly ash (WPFA) as a binder for soil stabilization. The mineralogical characterization shows the presence of free lime, as well as some non-reactive and cementitious phases. The hydration of lime is an expansive reaction and can be problematic in soil stabilization. Therefore, to study its effect on stabilized soil, an in-house experimental set-up is proposed to measure the possible expansion. Furthermore, to study the effect of water reduction and delay tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Fly ash is a material that is increasingly being used as a cement alternative in concrete mixtures and for soil stabilization [ 25 , 27 , 29 , 36 , 38 , 40 , 42 , 54 ]. The addition of fly ash is one of the methods to stabilize soil because fly ash is a pozzolan, in which it can bind to minerals in soil and make the soil stable, so as to reduce the swell shrinkage of the soil and improve soil strength [ 41 , 42 , 44 , 46 , 54 , 69 , 70 , 71 , 72 , 73 ].…”
Section: Soil Stabilization By Conventional Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fly ash is a material that is increasingly being used as a cement alternative in concrete mixtures and for soil stabilization [ 25 , 27 , 29 , 36 , 38 , 40 , 42 , 54 ]. The addition of fly ash is one of the methods to stabilize soil because fly ash is a pozzolan, in which it can bind to minerals in soil and make the soil stable, so as to reduce the swell shrinkage of the soil and improve soil strength [ 41 , 42 , 44 , 46 , 54 , 69 , 70 , 71 , 72 , 73 ].…”
Section: Soil Stabilization By Conventional Methodsmentioning
confidence: 99%
“…It entails compacting the soil in order to change its resistance, compressibility, permeability, and porosity [ 27 , 28 ]. Mechanical stabilization of a material is typically accomplished by adding another substance, which is fly ash or GGBFS, that enhances the grading or reduces the plasticity of the original material [ 28 , 29 , 30 ]. The original material’s physical qualities will be altered, but no chemical reaction will occur [ 26 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A precise displacement device was used to measure the swelling/shrinkage in the soil samples as described in previous work [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Authors (Khalid, 2012) have discovered, that clay soil stabilized using 10 % WSA considered effective to enhance clay soil strength for long periods and to enhance the CBR value. Other research results (Baloochi, 2020) have shown that use of wastepaper fly ash as a main binder is well suited for soil stabilization, although care should be taken to avoid possible soil expansion.…”
Section: Introductionmentioning
confidence: 99%